1974
DOI: 10.4098/at.arch.74-20
|View full text |Cite
|
Sign up to set email alerts
|

Selection of browse twigs by moose

Abstract: The relative selectivity by moose of twigs from 26 browse species was tested in a small enclosure from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Fifteen peaks were found that correspond to at least 15 plant species (24 maximum). Among plant species detected from stools, there were gymnosperms and angiosperms that have been previously reported in moose diet (Dzięciołowski 1974; Morow 1976; Belovsky 1981) by traditional methods (Table 1). One peak (59 bp) was not identified.…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…Fifteen peaks were found that correspond to at least 15 plant species (24 maximum). Among plant species detected from stools, there were gymnosperms and angiosperms that have been previously reported in moose diet (Dzięciołowski 1974; Morow 1976; Belovsky 1981) by traditional methods (Table 1). One peak (59 bp) was not identified.…”
Section: Resultsmentioning
confidence: 84%
“…Indeed, Taberlet et al (2007) suggested that the P6 loop will become the marker of choice for degraded DNA and diet studies based on feces (see also Kowalczyk et al 2011; Pompanon et al 2012). As many as 15 different peaks were identified from moose stools that correspond to 15–24 plant species (Table 1 of the Supplementary Material), including gymnosperms and angiosperms that have been previously reported in its diet (Dzięciołowski 1974; Morow 1976; Belovsky 1981). Different plant species were also successfully identified in the roe deer and red deer stool samples (19–32 and 19–29, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies carried out in Poland (Morow 1976) indicated high moose preferences for pine and willow in winter. However, Dzięciołowski (1974) classified Pinus sylvestris as a food of second choice.…”
Section: Introductionmentioning
confidence: 99%